A inserção dos egressos do Pronatc do IFRS - Campus Sertão no mercado de trabalho - Colombelli, Valéria Cristina Schu (2016)
This work aims to contribute to the evaluation of Access National Program for Education and Employment (Pronatec), through a case study with graduates of technical courses offered at the Federal Institute of Rio Grande do Sul - Campus Hinterland, as well as with employers of these professionals. The importance of treating this issue meets the public policies implemented by the Federal Government, together with the Ministry of Education, with the aim to boost the growth and development of the country. Thus institutionalized several actions, among which: increase the number of vacancies of vocational education to meet the low-income youth, targeting the demands of economic sectors and reach most of the municipalities that do not have access to training institutions the professional trajectory of graduates interviewed, as well as the difficulties encountered by them during the course and in the integration process to the labor market are recomposed. In addition, they present some suggestions for improvement for the courses offered, according to the interviewees. Thus, the research of the need to have a diagnosis on the concept that the IFRS - Campus Hinterland has as a promoter of regional development and the importance of a definition of resource policy, as well as the need for research and to provide services to the regional community a literature review was conducted that included laws that refer to vocational education network, as also some authors as Belloni (2001), Fonseca (1961, 1986), Frigotto (1995, 2000, 2004, 2005), Shiroma ( 2002), among others, to study this issue. Questionnaires were applied to former students who attended the technical courses Pronatec in IFRS - Campus Hinterland and interviewed employers of such graduates. Three categories were produced based on the material: the quality of education, citizenship and autonomy for emancipation and local clusters. These categories have helped us to reach three conclusions which we consider important, from the replies of the graduates and employers: The first finding was that both graduates, as employer, even understanding that the teaching quality of the courses was excellent or good, they reported the need to increase the amount or time of practical classes in the subjects; The second conclusion was that the technical progress made through the program, not only served for the training of graduates, but also to encourage them to continue their studies. And finally, another important fact was found during the studies was that the number of dropouts was high throughout the course.